Clinical study on cystic swellings of the scrotum in adults in a tertiary care hospital - Kemparaj, Thammegowda; Mathew, Joseph (International Surgery Journal, 2017)
Background: Cystic swellings of the scrotum are common clinical entities that surgeons encounter in daily practice. Males of all ages are affected. Today, considerable heterogeneity exists in their treatment. This study sought to identify the prevalence and patterns of presentation of these swellings in adults and evaluate the different modalities of surgical management. Methods: A cross-sectional study was undertaken from January 2013 to December 2016. A total of 186 patients fulfilling the inclusion criteria were included. Data was collected using a proforma. All patients were managed surgically. Results: Majority of cases (28%) were observed between 41-50 years (mean age 43.9 years). In 71%, mode of presentation was a painless, gradually progressive swelling. Mean duration of symptoms was 17.3 months. Primary vaginal hydrocele was the commonest swelling encountered (in 73.1%). Jaboulay’s procedure was undertaken in 75.2% of patients. Lord’s plication was associated with a comparatively shorter operative time, lesser postoperative scrotal edema and a shorter hospital stay. Epididymal cysts accounted for 19.4% and were managed by excision. The most common complication observed irrespective of surgery performed was scrotal edema (in 36%). Hematoma and infection were less frequently observed. Patients were followed-up for a mean period of 1.8 months. No recurrences were detected during this period. Conclusions: Cystic swellings of the scrotum are conditions predominantly affecting middle-aged males. Among these, primary hydrocele is the commonest. Although Lord’s plication is simpler and gives good results with fewer complications, Jaboulay’s procedure remains the gold standard for surgical management of hydrocele.